RARE EARTH ELEMENTS AS INDICATORS OF FORMATION CONDITIONS OF PALEOPROTEROZOIC METASEDIMENTARY ROCKS - Shatrov V.A. (My University, 2004)
Ascertaining the formation conditions of Precambrian metasedimentary rocks is difficult, and geochemical methods are commonly used in this respect. The application of rare earth elements (REEs) is based on the concept of their different forms of migration in water (suspension, dissolved compounds, or absorbed complex) giving rise to fractionation of REEs during the primary sedimentation and their inert behavior at the early stages of metamorphism. In this work, REEs are subdivided into LREE (La-Pr), MREE (Nd-Dy), and HREE (Ho-Lu, Y). HREEs prevail in the central parts of basins, while LREEs commonly accumulate in the near-shore environment. The Paleoproterozoic Kursk and Krivoi Rog groups from the Voronezh Crystalline Massif and Ukrainian Shield, with their unique iron ore reserves, are the subjects of this investigation. The possibility of facies reconstruction of the deposition of jaspilites (hornfels, according to Yu.A. Balashov) with the aid of REE distribution is based on the idea that they had a chemogenic sedimentary origin with mobilization of material in the process of continental crust formation and its redeposition in the final sedimentary basins.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская